A novel approach to improve handover performance. (7th May 2019) - Verma, Jyoti; Gupta, Sunanda; Manhas, Pratima; Arora, Vasudha
Nowadays, mobile communications have heterogeneous wireless networks offering variable coverage and quality of service (QoS). The availability of alternatives generates a problem of occurrence of unnecessary handoff that results in wastage of network resources. In order to maintain seamless mobility, service continuity and optimise usage of network resources, it is desirable to minimise handover failures and unnecessary handovers. In this paper, a handover necessity estimation algorithm is introduced. This algorithm is made up of two modules. The first module estimates handoff necessity. It involves received signal strength (RSS) prediction, travelling distance estimation and velocity estimation. In a second module, candidate networks are discovered from the available networks. Based upon the predicted future values of RSS and travelling distance inside the wireless local area network (WLAN), the proposed algorithm improves the probability of unnecessary handoff and handover failures.